Survival after radiotherapy versus radical cystectomy for primary muscle‐invasive bladder cancer: A Swedish nationwide population‐based cohort study. (1st April 2019) - Häggström, Christel; Garmo, Hans; de Luna, Xavier; Van Hemelrijck, Mieke; Söderkvist, Karin; Aljabery, Firas; Ströck, Viveka; Hosseini, Abolfazl; Gårdmark, Truls; Malmström, Per‐Uno; Jahnson, Staffan; Liedberg, Fredrik; et al.
Abstract: Background: Studies of survival comparing radical cystectomy (RC) and radiotherapy for muscle‐invasive bladder cancer have provided inconsistent results and have methodological limitations. The aim of the study was to investigate risk of death after radiotherapy as compared to RC. Methods: We selected patients with muscle‐invasive urothelial carcinoma without distant metastases, treated with radiotherapy or RC from 1997 to 2014 in the Bladder Cancer Data Base Sweden (BladderBaSe) and estimated absolute and relative risk of bladder cancer death and all‐cause death. In a group of patients, theoretically eligible for a trial comparing radiotherapy and RC, we calculated risk difference in an instrumental variable analysis. We have not investigated chemoradiotherapy as this treatment was not used in the study time period. Results: The study included 3 309 patients, of those 17% were treated with radiotherapy and 83% with RC. Patients treated with radiotherapy were older, had more advanced comorbidity, and had a higher risk of death as compared to patients treated with RC (relative risks of 1.5‐1.6). In the "trial population, " all‐cause death risk difference was 6 per 100 patients lower after radiotherapy at 5 years of follow‐up, 95% confidence interval −41 to 29. Conclusion(s): Patient selection between the treatments make it difficult to evaluate results from conventionally adjusted and propensity‐score matched survival analysis. When taking into account unmeasured confounding by instrumental variable analysis, no differences in survival was found between the treatments for a selected group of patients. Further clinical studies are needed to characterize this group of patients, which can serve as a basis for future comparison studies for treatment recommendations. Abstract : In this study, we investigated the risk of death after radiotherapy as compared to radical cystectomy for muscle‐invasive bladder cancer, and found different results for different methods used. For a selected group of patients, we found similar survival after the two treatments; this patient group could serve as a basis for future comparison studies.